2004
DOI: 10.1007/s10434-004-1163-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Examination of Sentinel Nodes in the Initial Assessment of Patients With Primary Cutaneous Melanoma

Abstract: These results suggest that a targeted US examination of SLNs can detect metastatic melanoma deposits down to approximately 4.5 mm in diameter. However, most metastatic melanoma deposits in SLNs are considerably smaller than this at the time of initial staging, and US therefore cannot be considered cost-effective in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 17 publications
5
36
2
1
Order By: Relevance
“…The Melanoma Institute Australia, University of Sydney (former name: Sydney Melanoma Unit) has previously reported that ultrasound is able to reliably detect SLN metastases that are greater than 4.5 mm in diameter. This is in accordance with results of a former study of Starrit et al [21] who performed SLN ultrasound after lymphoscintigraphy in 304 patients presenting with primary cutaneous melanomas. Histopathologic examination revealed 33 positive SLNs in 31 patients, and, seven out of this group were suspicious for metastases by ultrasonography.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The Melanoma Institute Australia, University of Sydney (former name: Sydney Melanoma Unit) has previously reported that ultrasound is able to reliably detect SLN metastases that are greater than 4.5 mm in diameter. This is in accordance with results of a former study of Starrit et al [21] who performed SLN ultrasound after lymphoscintigraphy in 304 patients presenting with primary cutaneous melanomas. Histopathologic examination revealed 33 positive SLNs in 31 patients, and, seven out of this group were suspicious for metastases by ultrasonography.…”
Section: Discussionsupporting
confidence: 82%
“…However, the results of the preoperative detection of SLN metastases by high resolution ultrasound are controversial [19,20,21,22,23,24,25,26]. High-resolution ultrasonography without Doppler sonography had been evaluated as diagnostic tool but failed to replace the SLNB, especially as far as the detection of micrometastases is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the literature, the sensitivity in our hands (51%) is significantly higher than previously reported rates, which differ from 4% to 39% [24][25][26][27][28][29]. In these relatively small series, Starritt et that high-resolution ultrasound (HRUS) yielded a sensitivity of 12% (2/17) [28].…”
Section: Discussioncontrasting
confidence: 52%
“…Both methods, however, are inferior to sentinel lymph node biopsy in sensitivity and specificity. Prior to LND, distant metastases shall be ruled out [108,109,113,314,315].…”
Section: Therapeutic Lymphadenectomymentioning
confidence: 99%